Peran Badan Usaha Milik Daerah dalam Meningkatkan Kesejahteraan Masyarakat (Studi Pembentukan Perusahaan Daerah di Aceh) - Teuku Ahmad Yani (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: Both province and regional may establish Regional or Provincial Company that can be formed as Regional Company or Limited Company. The establishment of such company shold be based on local regulation aiming to collect the revenue supporting the development and public facilities. The establishment of such company must be in obligatory implementation and optinal matter owned. The option is based on special patent owned by the area. Therefore, the creation of the company should be started by acceptable study regarding the field of the company. The Role of Regional Company in Improving Society Welfare (A Study on Stablishing Regional Company in Aceh)